PERBANDINGAN STRATEGI PEMASARAN POLITIK PADA PEMILIHAN KEPALA DAERAH DI KABUPATEN KENDAL TAHUN 2010 DAN BATANG TAHUN 2011 STUDI KASUS PADA PASANGAN YAKIN DAN BERSUSILA - Nur Muhibbatul Ulya; Muhammad Adnan; Priyanto Harsasto (Journal of Politic and Government Studies, 2014)
General election widely followed by the incumbent candidate, as it did in election disctrict regional head in Kendal at year 2011 and Batang at year 2012, in which one candidate is the wife of the regent 2 previous period and the two regents were eventually convicted of corruption . The purpose of the study was to determine the political marketing of YAKIN and BERSUSILA, and the factors that influence YAKIN victory and the factors that influence defeat bereft of BERSUSILA.This type of research is qualitative, where the information is obtained from the prospective candidates, team succession, and the voting public through interviews. Data were analyzed using qualitative analysis with content analysis approach .The results of the study are (1) that political marketing is done by YAKIN and BERSUSILA basically not much different. (a) Segmentation relatively equally YAKIN and BERSUSILA. YAKIN more than support elements of society bereft of decency. YAKIN and BERSUSILA are equally promoted by political parties PDIP. Strategies used by YAKIN and BERSUSILA to demonstrate competence and charisma themselves with education degrees and titles include religion, as well as using religious accessories. YAKIN and BERSUSILA also visited religious leaders and raise the issue of gender. Strategies YAKIN and BERSUSILA get swing voters are forming a map of the vote, a solid area, less, and will be lost, as well as form a coalition (b) YAKIN and BERSUSILA sound alike targeting at least 50 % by district with the focus of the campaigns in the villages. (c) In general, the products politics of YAKIN and BERSUSILA not much different. Common vision and mission impressed and difficult to apply. YAKIN and BERSUSILA also uses general pattern and not something new. YAKIN and BERSUSILA are equally trying to portray themselves as a couple of candidates who have a strong faith and a personal meet the requirements of Islam. They also